Turkey : 2017 Article IV Consultation-Press Release; Staff Report; and Statement by the Executive Director for Turkey. (IMF Staff Country Reports; Country Report, 2017)
This 2017 Article IV Consultation highlights that growth in Turkey has slowed following a strong performance in 2015. Investment is weak amid heightened uncertainty and a sharp deceleration of credit growth. Inflation has moderated but is still well above target. The current account deficit remains sizeable, as the decline in tourism offsets savings from low energy prices. Progress on structural reforms has been slow. Over the medium term, growth is projected to firm at about 3.5 percent. Inflation is expected to stay above target and the current account deficit to remain sizeable.